IODIMETRY-PHOTOMETRIC DETERMINATION of periodate, iodate And bromate In WATER SOLUTIONS: UDC 543.42.062 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2018)
A simple and accurate three-step procedure for sequential spectrophotometric determinations of periodate, iodate and bromate in aqueous media has been developed. At the first stage the determination of periodate is based on the selective oxidation of the excess amount of iodide at pH=4,8 to produce iodine (triiodide), that can be found by spectrophotometric detection (лmax=350 nm). After detecting the analytical signal, iodine is removed from the solution by sorption on the polyurethane foam. In the second stage the determination of iodate is based on the selective oxidation of iodide at pH=3,0 to produce iodine (triiodide), that also can be found by spectrophotometric detection (лmax=350 nm). After detecting the analytical signal, also iodine is removed from the solution by sorption on the polyurethane foam. In the third stage the determination of bromate is based on the selective oxidation of iodide at pH=1,0 to produce iodine (triiodide), that also can be found by spectrophotometric detection (лmax=350 nm).It has been established that the equilibrium in the reaction (ІО4– + 7І– + 8Н+ → 4І2 +4Н2О) is established in 3 minutes at pH=4,8. The equilibrium in the both reactions (ІО3– + 5І– + 6Н+ → 3І2 +3Н2О and BrО3– + 6І– + 6Н+ → 3І2 +Br– +3Н2О) is established in 7 minutes at pH=3.0 and at pH=1,0 respectively. It was found that oxohalogates are quantitatively converted to I2 with ~ 100-fold molar excess iodide at appropriate optimal pH values.Schematically, the determination of IO4–, IO3– and BrO3– in their combined presence can be represented as follows:ІО4– + ІО3– + BrО3– ІО3– + BrО3–+ І3– (SP)  PUF.І2 (sorbent is discarded) + ІО3– + BrО3– BrО3– + І3– (SP)  PUF.І2 (sorbent is discarded) + BrО3–  І3– (SP),where SF is spectrophotometry in a solution at 350 nm: PUF is the polyurethane foamBased on the data obtained, the model mixtures of periodate, iodate and bromate by sequential iodiometry-photometric method were analyzed. The error of determination in mixtures of each oxo-halogenate did not exceed 5%.
Keywords: periodate, iodate, bromate, photometry